(untitled) (Research, Society and Development, 2023)
Objective: The purpose of this paper is to discuss the surgical methods available for the treatment of MRONJ, pointing out their advantages and limitations. Methodology: An integrative review of the literature was performed by searching the PubMed virtual database using the MeSH term "bisphosphonate associated osteonecrosis of the jaw/surgery" and including 26 publications. Results: Surgical intervention is presented as a treatment option in an attempt to reduce disease progression with the recognition that this early intervention may predict beneficial outcomes for the patient. Surgical approaches confer superior treatment outcomes over conservative treatments, with success rates of 80-90% and 10-62%, respectively. To establish treatment, consideration should be given to therapy for removing nonhealing exposed bone, which can be accomplished through curettage, sequestrectomy, and surgical resection. When approaching soft tissue, different flaps can be performed, according to their indications. Conclusion: Surgical treatment has shown maintenance of mucosal coverage, improved quality of life, and quick resumption of antiresorptive therapy for all stages of the disease, with high rates of therapeutic success. However, continued efforts should be encouraged to investigate the best treatment for this pathology.